The adenosine A2A receptor in human sperm: its role in sperm motility and association with in vitro fertilization outcomes - Chen, Houyang; Xing, Genbao; Xu, Wenqing; Chen, Ying; Xia, Leizhen; Huang, Hua; Huang, Jialv; Hong, Qing; Luo, Tao; Wang, Hao; Wu, Qiongfang (Frontiers in Endocrinology, 2024)
Background: The involvement of ATP and cAMP in sperm function has been extensively documented, but the understanding of the role of adenosine and adenosine receptors remains incomplete. This study aimed to examine the presence of adenosine A2A receptor (A2AR) and study the functional role of A2AR in human sperm. Methods: The presence and localization of A2AR in human sperm were examined by western blotting and immunofluorescence assays. The functional role of A2AR in sperm was assessed by incubating human sperm with an A2AR agonist (regadenoson) and an A2AR antagonist (SCH58261). The sperm level of A2AR was examined by western blotting in normozoospermic and asthenozoospermic men to evaluate the association of A2AR with sperm motility and in vitro fertilization (IVF) outcomes. Results: A2AR with a molecular weight of 43 kDa was detected in the tail of human sperm. SCH58261 decreased the motility, penetration ability, intracellular Ca2+ concentration, and CatSper current of human sperm. Although regadenoson did not affect these sperm parameters, it alleviated the adverse effects of SCH58261 on these parameters. In addition, the mean level of A2AR in sperm from asthenozoospermic men was lower than that in sperm from normozoospermic men. The sperm level of A2AR was positively correlated with progressive motility. Furthermore, the fertilization rate during IVF was lower in men with decreased sperm level of A2AR than in men with normal sperm level of A2AR. Conclusions: These results indicate that A2AR is important for human sperm motility and is associated with IVF outcome.